EVALUASI DAN PERUMUSAN STRATEGI TELKOM FLEXI DENGAN MENGGUNAKAN MODEL DAVID - A., Anggara Hayun (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
TelkomFlexi is a business unit from PT Telkom Divre V East Java that is moving in cellular industry field. Cellular industry is an industry that having tight competitor so every company should fight to continue its sustainability. To get continue the live, TelkomFlexi have are appropriate strategy. To make good strategic management model, they have to execute strategic management model review. According to the strategic management model review, the good model is David model. The application of David model is in three stages, input stage, matching stage, and decision stage.